Inhibitory Effect of Ulva fasciata and Desmarestia viridis on the Production of Nitric Oxide, Prostaglandin E2, and Pro-inflammatory Cytokines in RAW 264.7 Cells - Min-Jin Kim, Kyong-Wol Yang, Wook Jae Lee, Sang Suk Kim, Nam Ho Lee and Chang-Gu Hyun (Journal of Applied Pharmaceutical Science, 2013)
Nitric oxide (NO) and prostaglandin (PG)E2, known inflammatory mediators, are critically involved in the pathogenesis of a large number of human inflammatory diseases. Therefore, a search of inducible nitric oxide synthases (iNOS) and cyclooxygenase 2 (COX-2) selective inhibitors is a useful strategy to find functional substances to alleviate inflammatory disease. In our search for anti-inflammatory ingredients, we found that extracts of Ulva fasciata (UFE) and Desmarestia viridis (DVE) inhibit the generation of NO and PGE2 in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophage cells. U. fasciata and D. viridis were extracted with 80% ethanol and then partitioned successively with ethyl acetate. The ethyl acetate fractions are effective dose-dependent inhibitors of LPS-induced NO and PGE2 synthesis in RAW 264.7 cells. To test the inhibitory effects of UFE and DVE on pro-inflammatory cytokines, we performed ELISA assays for tumor necrosis factor (TNF)-α, IL (interleukin)-1β, and IL(interleukin)-6 in LPS-stimulated RAW 264.7 macrophage cells. In these assays, the UFE and DVE showed a dose-dependent decrease in the production of TNF-α, IL-1β, and IL-6. As a preliminary study of the anti-inflammatory mechanism, we determined, using the Western blot analysis, whether or not UFE and DVE inhibit the degradation of I-kappa-B-alpha (IκB-α). Our results indicate that UFE and DVE indeed prevent the degradation of IκB-α, in a dose-dependent manner. Based on these results, we suggest that extracts of U. fasciata and D. viridis be considered candidates for anti-inflammatory agents for human use.
Keywords: Cytokine, Desmarestia viridis, inflammation, nitric